Stylistic Features in Ibn Al-Muqaffa’ al-Adab al-Sagheer and al-Adab al-Kabeer Arguments - Hudieb, Firyal (Dirasat: Human and Social Sciences, 2021)
Ibn Al-Muqaffa’ literature in al-Adab al-Sagheer and al-Adab al-Kabeer aims at convincing the reader to make change in his code of ethics, which shape the relationship between the psych and the others. This made Ibn Al-Muqaffa’ follow a technique relying on the use of arguments and a pragmatic style to achieve his goals and make a change in the reader’s code of ethics. This research investigates the argumentative and stylistic features Ibn Al-Muqaffa’ relied on in his literature.This research reveals that Ibn Al-Muqaffa’ relied on three styles in his argumentative presentation, mainly: condition, preference, and comparison. He woven the three styles together to achieve his goals.